2010
DOI: 10.1083/jcb.201004118
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 and dynein at the nuclear envelope mediate the bidirectional migrations of nuclei

Abstract: The molecular motors kinesin-1 dynein navigate migrating nuclei around cytoplasmic roadblocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 73 publications
(132 reference statements)
4
173
0
Order By: Relevance
“…Because F-actin and microtubule motors are known to exert forces on the nuclear surface (2,5,6,18,(25)(26)(27)(28), it is surprising that they do not contribute to mechanical homeostasis of the nucleus. It seems that these cytoskeletal networks have the primary role of generating active forces through motor activity on the nuclear surface to position it.…”
Section: Discussionmentioning
confidence: 99%
“…Because F-actin and microtubule motors are known to exert forces on the nuclear surface (2,5,6,18,(25)(26)(27)(28), it is surprising that they do not contribute to mechanical homeostasis of the nucleus. It seems that these cytoskeletal networks have the primary role of generating active forces through motor activity on the nuclear surface to position it.…”
Section: Discussionmentioning
confidence: 99%
“…Since Csm4 is the likely KASH protein linking telomeres to cytoskeletal actin in budding yeast Wanat et al 2008;Fridolfsson and Starr 2010), we tested if the csm4D mutation in combination with nup2D would give a synthetic phenotype similar to nup2D ndj1D. First we looked at the sporulation efficiency of the single and double mutants, and found that while 92% of nup2D and 76% of csm4D cells produced two or more spores (n = 200), only 1% of nup2D csm4D double mutant cells (n = 200) produced spores, similar to what we observed for nup2D ndj1D (1.5%, n = 200; Table 1).…”
Section: Dsb Levels Are Elevated In the Absence Of Nup2mentioning
confidence: 99%
“…In unc-84 or unc-83 mutant embryos, the elongation and intercalation of cells proceeds normally, but the nuclei fail to move from their initial positions. 13,15 As the embryo continues to develop, mutant nuclei that fail to migrate are passively pushed toward the dorsal midline by underlying muscle cell migrations and can be observed by DIC microscopy in the dorsal cord of the L1 larva. 15 In the adult hypodermal syncytia, UNC-84 interacts with ANC-1, which interacts with actin to anchor nuclei .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In Caenorhabditis elegans somatic cells, the SUN protein UNC-84 interacts with the KASH protein UNC-83, which recruits microtubule motors kinesin and dynein to facilitate nuclear migration. 12,13 In the early embryo, hypodermal precursors line up in 2 rows across the dorsal midline. As cells intercalate and elongate to form one row of 16 cells, the nuclei migrate contra-laterally to the opposite side of the dorsal midline.…”
Section: Introductionmentioning
confidence: 99%